Comparison of conservative management and juvenile pubic symphysiodesis in the early treatment of canine hip dysplasia - Vezzoni, A.; Dravelli, G.; Vezzoni, L.; De Lorenzi, M.; Corbari, A.; Cirla, A.; Nassuato, C.; Tranquillo, V. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Objectives: To evaluate the efficacy of juvenile pubic symphysiodesis (JPS) in a clinical setting for the early treatment of canine hip dysplasia (CHD), and to identify its indications and contraindications. Methods: The final degree of CHD using the FCI (Fédération Cynologique Internationale) CHD classification in 5 Grades (A, B, C, D, E) was assessed at skeletal maturity in two homogeneous groups of dogs assessed at the age of 14 to 22 weeks and selected according to their susceptibility to CHD; one group was treated with JPS and one group was conservatively managed. Two hundred seventeen puppies completed the study; 81 were treated with JPS (group 1) and 76 were conservatively managed (group 2). A third group of 60 puppies with normal hips was followed as a negative control group. Results: In group 1, 43.2% of the puppies had regression or a lack of progression of the disease in the final evaluation (Grade A & B), 25.9% had mild CHD (Grade C) and 30.9% had moderate and severe CHD (Grade D & E). In group 2, 23.6% of the puppies did not show any development of the disease (Grade A & B), 21.1% had mild CHD (Grade C) and 55.3% developed moderate to severe CHD (Grade D & E). Further investigation was done by comparing the severity of early signs of susceptibility to CHD with the final FCI Grades at adulthood in both groups. Clinical significance: The JPS procedure increased the odds of arresting or limiting the progression of CHD in mild to moderate grades of CHD, while it was less effective or ineffective in more severe forms.
Keywords: Dog; hip dysplasia; CHD; juvenile pubic symphysiodesis; JPS